Linking Emotional Intelligence with Qur’an Memorization Proficiency: Evidence from MTsS Dayah Insan Qur'ani Aceh Besar Students - Musfirah, AM. Riska; Mahmud, Salami; Zubaidah; Pranajaya, Syatria Adymas (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study investigates the correlation between emotional intelligence (EQ) and the ability to memorize the Qur’an among students of MTsS Dayah Insan Qur’ani Aceh Besar. The study addresses the lack of empirical research examining non-cognitive factors that influence Qur’anic memorization success in Islamic education. Using a correlational quantitative approach, data was collected through observation, questionnaires, and documentation from 35 tahfidz students, representing 20% of the total population of 176 students. Based on the results of random sampling, the selected sample came from grades VIII and IX who were active in tahfidz and muroja'ah activities. Descriptive results show that students’ emotional intelligence and Qur’an memorization ability are generally in the moderate category. Reliability testing indicated high internal consistency (EQ scale α = 0.886; memorization scale α = 0.871). Pearson’s correlation analysis produced a strong positive relationship (r = 0.694, p < 0.01), indicating that students with higher EQ tend to achieve more extensive memorization. Practically speaking, the results of this study recommend that teachers in tahfidz learning integrate and strengthen the development of students' emotional aspects along with cognitive training so that the target of memorizing the Qur'an can be achieved optimally. This finding reinforces the understanding that emotional intelligence plays a significant role in the success of tahfidz-based Islamic education.